The novel : an alternative history : beginnings to 1600 - Moore, Steven (New York (NY) : Continuum, 2010)
A comprehensive history - and controversial reappraisal - of the world's most popular and innovative literary form.
The ancient novel: Egyptian -- Mesopotamian -- Hebrew -- Greek -- Roman -- Christian -- The medieval novel: Irish -- Icelandic -- Byzantine -- Jewish -- Arthurian -- The Renaissance novel: Italian -- Spanish -- French -- English -- The Mesoamerican novel -- The Eastern novel: Indian -- Tibetan -- Arabic -- Persian -- The Far Eastern novel: Japanese -- Chinese.
Keywords: Fiction -- History and criticism; genret; kertomakirjallisuus; kirjallisuudentutkimus; romaanit